Evaluación de un tratamiento para la disminución de precipitaciones de sólidos en el agua de producción del Campo Quillacinga (2022)
The objective of this work is to evaluate an effective solution for the reduction of precipitation such as calcium carbonates, chloride ions, sulfur and bicarbonate in the production water of the Quillacinga Field, recognizing the importance of providing a solution to this problem with respect to to the productive affectation that this type of problem can generate.